Neonatal mid upper arm circumference as surrogate of birth weight - Agrawal, Ankit; Gaur, Ajay; Ambey, Ravi (International Journal of Contemporary Pediatrics, 2020)
Background: Recording an accurate birth weight by primary health worker has been a problem in rural areas, leading to search for an alternative, inexpensive, age independent and noninvasive method to predict newborn birth weight and wellbeing. With this background I aimed to found out whether the neonatal-MUAC is associated with birth weight or not? Methods: This hospital based prospective observational study was conducted in SNCU and postnatal ward, Kamla Raja Hospital, G.R. Medical College, and Gwalior (M.P). A total of 1303 newborns were included in the study. The Mid upper arm circumference (MUAC) of newborns were taken and Birth weight recorded were filled in a proforma. Results: Total 1303 neonates were evaluated. The mean MUAC and birth weight in preterm was found to be 1854.80±387.3 and 7.47±0.9 as compared to full term newborn having mean birth weight(2818.95±328.1) and mean MUAC (9.58+0.7).The Pearson coefficient of correlation between neonatal MUAC (N-MUAC) and birth weight was found to be r= 0.987 and p<0.01. Birth weight can be predicted from regression equation: Birth weight (gms)=422.99 (N-MUAC) + (-1272.66). Cut-off value of neonatal mid upper arm circumference (N-MUAC) was found to be 8.85cm to predict low birth weight newborn. Conclusions: Birth weight of newborn can be predicted from neonatal mid upper arm circumference (N-MUAC) in areas where the conventional scale are not easily available for measuring the birth weight of newborn.